Group living in squamate reptiles: a review of evidence for stable aggregations - Gardner, Michael G.; Pearson, Sarah K.; Johnston, Gregory R.; Schwarz, Michael P. (Biological reviews of the Cambridge Philosophical Society, 2016)
ABSTRACT How sociality evolves and is maintained remains a key question in evolutionary biology. Most studies to date have focused on insects, birds, and mammals but data from a wider range of taxonomic groups are essential to identify general patterns and processes. The extent of social behaviour among squamate reptiles is under‐appreciated, yet they are a promising group for further studies. Living in aggregations is posited as an important step in the evolution of more complex sociality. We review data on aggregations among squamates and find evidence for some form of aggregations in 94 species across 22 families. Of these, 18 species across 7 families exhibited ‘stable’ aggregations that entail overlapping home ranges and stable membership in long‐term (years) or seasonal aggregations. Phylogenetic analysis suggests that stable aggregations have evolved multiple times in squamates. We: (i) identify significant gaps in our understanding; (ii) outline key traits which should be the focus of future research; and (iii) outline the potential for utilising reproductive skew theory to provide insights into squamate sociality.